2000
DOI: 10.1121/1.429607
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aging on horizontal plane sound localization

Abstract: An experiment was conducted to determine the effect of aging on sound localization. Seven groups of 16 subjects, aged 10-81 years, were tested. Sound localization was assessed using six different arrays of four or eight loudspeakers that surrounded the subject in the horizontal plane, at a distance of 1 m. For two 4-speaker arrays, one loudspeaker was positioned in each spatial quadrant, on either side of the midline or the interaural axis, respectively. For four 8-speaker arrays, two loudspeakers were positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
89
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 33 publications
8
89
1
2
Order By: Relevance
“…The lack of an age effect for single-sound localization may be explained by relatively low task difficulty, and the fact that the older group included mainly middle-aged subjects. In seeming opposition to this, Abel et al (2000) have shown that correct single-source identification judgments decreased as early as in the third decade of life. However, the proportion of correct identifications analysed by these authors may involve factors different from the constant error used here as a measure of performance.…”
Section: Age-related Differencesmentioning
confidence: 90%
See 4 more Smart Citations
“…The lack of an age effect for single-sound localization may be explained by relatively low task difficulty, and the fact that the older group included mainly middle-aged subjects. In seeming opposition to this, Abel et al (2000) have shown that correct single-source identification judgments decreased as early as in the third decade of life. However, the proportion of correct identifications analysed by these authors may involve factors different from the constant error used here as a measure of performance.…”
Section: Age-related Differencesmentioning
confidence: 90%
“…However, the proportion of correct identifications analysed by these authors may involve factors different from the constant error used here as a measure of performance. Also, an anechoic environment was used here, while the experiments of Abel et al (2000) were conducted in a semireverberant environment, thus involving phenomena such as echo suppression (Cranford et al, 1990). Because echoes could have been distracting, the approach of Abel et al (2000) may be comparable with the present distractor-sound condition, in which deterioration in performance was obtained at middle age (cf.…”
Section: Age-related Differencesmentioning
confidence: 99%
See 3 more Smart Citations